Development and fabrication of power operated groundnut decorticator cum separator - ANITHA NAIR A GANESAN V SUSHAMA V SWAPNAM S; Er. V.R Ramachandran (Guide) (Tavanur 1992 Department of Farm Power Machinery and Energy)
Development and fabrication of power operated groundnut decorticator cum separator
Development and fabrication of power operated groundnut decorticator cum separator